THE MODEL FOR EVALUATION OF AVERAGE ANNUAL EFFECTIVE EXPOSURE DOSES OF CRITICAL GROUPS OF EASTERN URALS RADIOACTIVE TRACE ZONE POPULATION - O. S. Kravtsova (Радиационная гигиена)
The article shows the results of radiation hygienic survey of settlements located in the area of Eastern Urals radioactive trace generated after the accident at Production Association Mayak in 1957. It presents stochastic simulation of the internal exposure doses of the inhabitants of 4 settlements caused by local agricultural food products consumption. The article also offers the model for predictive evaluation of average annual effective exposure doses of the critical groups of Eastern-Urals radioactive trace zone population.